2013
DOI: 10.7860/jcdr/2012/5016.2673
|View full text |Cite
|
Sign up to set email alerts
|

ESBL, MBL and Ampc Lactamases Producing Superbugs – Havoc in the Intensive Care Units of Punjab India

Abstract: Background: An alarming rise in the rates of the antibiotic resistance has now become a serious and an increasingly common public health concern, with severe implications, especially in the intensive care units. A variety of ß-lactamases which include ESBLs, AmpC ß-lactamases and metallo-ß-lactamases, have emerged as the most worrisome mechanism of resistance among the gram negative bacteria, which pose a therapeutic challenge to the health care settings. Materials and Methods:The present study was aimed at kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
54
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 12 publications
19
54
6
Order By: Relevance
“…No previous study has investigated the prevalence of extended spectrum beta-lactamases resistance in burn infection in Gaza strip, Palestine. The incidence of ESBL in gram-negative isolates was 37.5% (15 out of 40 isolates) which is similar to many studies, particularly from India, which showed a high prevalence of ESBL-producers that reached 39.8% and 35.16% in burn patients, respectively [3,21] and lower than reported from in Iraq ( 61.5%) iamong gram-negative bacteria [22]. In Iran, 21% of A. baumannii isolates from burn patients were found to be ESBL-producers [23].…”
Section: Discussionsupporting
confidence: 64%
“…No previous study has investigated the prevalence of extended spectrum beta-lactamases resistance in burn infection in Gaza strip, Palestine. The incidence of ESBL in gram-negative isolates was 37.5% (15 out of 40 isolates) which is similar to many studies, particularly from India, which showed a high prevalence of ESBL-producers that reached 39.8% and 35.16% in burn patients, respectively [3,21] and lower than reported from in Iraq ( 61.5%) iamong gram-negative bacteria [22]. In Iran, 21% of A. baumannii isolates from burn patients were found to be ESBL-producers [23].…”
Section: Discussionsupporting
confidence: 64%
“…The prevalence of MBL in the present study is in concordance with the published literature [10,32]. Amongst the imipenem resistant Pseudomonas isolates 25% were MBL producers while mechanisms other than MBL production operated in the remaining 75% imipenem resistant isolates.…”
Section: Discussionsupporting
confidence: 82%
“…ESBL and AmpC production was maximum in E.coli followed by Klebsiella spp as observed in various reports worldwide [29]. This increased number of AmpC producers is in agreement with other works from India which reported 17.3% AmpC producers in Kolkata [10] and 22.9% by Bandekar et al [10]. This rising ESBL production poses a daunting challenge in gram negative antibiotic resistance, indicative of an ominous trend of more and more isolates acquiring the resistance mechanisms.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This has emerged as the most worrisome resistance mechanism posing a therapeutic challenge to the health care settings as they are capable of hydrolyzing a wide range of β-lactam antibiotics, notably the extended-spectrum penicillins, third and fourth generation cephalosporins, and the carbapenems (Oberoi L. et al, 2013) The confirmed ESβL-producing isolates should be reported as resistant to all penicillins, cephalosporins, and aztreonam to avoid therapy with antibiotics that may be clinically ineffective but bacteria producing these enzymes may not be recognized as they are falsely susceptible in routine tests as a result patients start receiving ineffective antibiotics which contributes to the spread of the pathogens with hidden resistance. Tests based on ceftazidime and cefotaxime tested alone and in combination with clavulanate are useful in ESBL detection but they may yield false positive results with Klebsiella pneumonia carbapenemase (KPCs) and hyper produced K1β-lactamaes (K1βL) and false negative results with isolates that coproduce a high level of AmpCβL.…”
Section: Introductionmentioning
confidence: 99%